Optimasi proses degumming minyak sawit mentah (DRPO) dengan response surface methodology (RSM) berbasis central composte design (CCD) - Jefri Pandu Hidayat; Rizka Lestari; Siti Munfarida; Andini Angelina Putri; Adrian Prananda Putra; Fidela Chosta; Ahmad Maulidi (Agroindustrial Technology, University of Trunojoyo Madura, 2025)
Crude palm oil (CPO) is widely used in various processed food products, especially cooking oil. Refining cooking oil involves high heating temperatures and the addition of bleaching earth, which aims to remove the sap and brown-red color. As a result, it can eliminate the carotene, which is not functionally used for good human metabolism. This research aims to remove sap and impurities in CPO by analyzing the optimal operation of heating temperature (60-80 °C) and phosphoric acid concentration (0.5-2 ml) and comparing the functional group change on the degumming process. The analytical method used was Response Surface Technology (RSM) by Central Composite Design (CCD) at Design Expert 12, which used carotene, density, and free fatty acid (FFA) responses. The results are optimal variables on heating temperature 80 °C and 2 ml of phosphoric acid concentration. The result of %FFA in DRPO was 1.917 %, the carotene was 381,350 ppm, and the density was 0.909 g/l. Heating temperature influences the FFA content, which is an important consideration. Higher temperatures can lead to an increase in FFA content. Indeed, lipase activation significantly affects the FFA content by accelerating the enzyme-catalyzed reaction. Apart from that, the addition of phosphoric acid affects the increase in FFA due to the non-reaction of phosphoric acid. The physicochemical characteristics of palm oil after the degumming process have not changed significantly, with the density before and after the degumming process still being in the range of (0.909–0.912) g/l. Group bonds have no change because the C-H and C=O group bonds in the main triglyceride compound. It requires a lot of energy to break the triglyceride cluster chains. The preliminary FFA model was revealed y=0.169(T)-0.1064(V)-1.5 to degummed reactor design, further.